Nanosilica composite asphalt mixtures performance-based design and optimisation using response surface methodology - Bala, N. (Taylor and Francis Ltd., 2018)
In recent times, the use of polymer nanocomposite for construction of durable asphalt mixtures has been gradually replacing the application of polymer-modified binders. In this investigation, the optimisation of nanosilica and binder content for nanocomposite-modified asphalt mixtures has been examined to obtain optimum quantities for high-performance properties. Response Surface Methodology (RSM) was applied for the optimisation based on central composite design (CCD). Interaction effects of two independent variable factors, nanosilica and binder content, on nanocomposite strength, volumetric and performance properties were analysed using CCD design. The responses were analysed using RSM, and models were developed to fit the experimental results for prediction of the responses. The results indicate that the individual effects of nanosilica and binder content are both important for performance improvement. Based on the numerical optimisation, 1.5 nanosilica and 5 binder content were found to be the optimal values. Also, the mean error obtained from optimisation results are all less than 5 for all responses, indicating that predicted values agree with experimental results and the developed models fit to the experimental results. Furthermore, the study concluded that for composite asphalt mixture design with high-performance properties, optimisation using RSM is a very good approach. Â© 2018 Informa UK Limited, trading as Taylor & Francis Group